Interplay between climate change and climate variability: the 2022 drought in Central South America (2024)
ABSTRACT:Since 2019, Central South America (CSA) has been reeling under drought conditions, with the last 4 months of 2022 receiving only 44% of the average total precipitation. Simultaneously to the drought, a series of record-breaking heat waves has affected the region. The rainfall deficit during October–November-December (OND) is highly correlated with the Niño3.4 index, indicating that the OND 2022 rainfall deficit is partly driven by La Niña, as observed in previous droughts in this region. To identify whether human-induced climate change was also a driver of the OND 2022 rainfall deficit, we analysed precipitation over the most impacted region. Our findings revealed a pattern of decreased rainfall over the past 40 years, although we cannot definitively conclude whether this trend exceeds what would be expected from natural variations. To clarify if this trend can be attributed to climate change, we looked at 1-in-20-year low rainfall events over the same region in climate models. The models show that the severity of low rainfall events decreases (i.e. they become wetter, the opposite of the trend observed in most weather records), although this trend is again not significant and is compatible with natural variability. Therefore, we cannot attribute the low rainfall to climate change. Moreover, our analysis of effective precipitation potential (evapotranspiration minus rainfall) shows that, in climate models, the increase in temperature does partly compensate for the increase in rainfall but only to offset the wetting, and does not lead to a significant climate change signal in effective precipitation. However, higher temperatures in the region, which have been attributed to climate change, decreased water availability in the models in late 2022, indicating that climate change probably reduced water availability over this period also in the observations, increasing agricultural drought, although this study did not quantify this effect. This means that even though the reduced rainfall is within the natural variability, the consequences of drought are becoming more severe due to the strong increase in extreme heat. The case of the OND 2022 rainfall deficit and the ongoing drought in CSA is a clear example of the interplay between climate variability and human-induced climate change. This shows the importance of considering not only those aspects associated with climate change but also climate variability in order to understand and attribute particular events or trends at the regional level.